Rancang Bangun Aplikasi Dekstop Sistem Persediaan Obat Pada Apotek (Studi Kasus : Apotek Assifa Lampung) - Yodhi Yuniarthe; Fatimah Fahurian; Icha Nuari (Universitas Mitra Indonesia, 2021)
AbstractPharmacy is one of the health service facilities in helping to achieve optimal health status for the community. Health services are every effort carried out individually or together in an organization to improve health, prevent and cure disease and restore individuals, families, groups and communities. Assifa Pharmacy is one of the pharmaceutical health service units that can help the public to obtain drugs, but currently at the Assifa pharmacy it has not been done computerized by recording, the data processing process takes time and often experiences inaccuracies or is slow in the search and report process. the data. With these problems, a desktop-based application is needed for drug supplies at pharmacies that can overcome existing problems. The results of the design of this study are desktop-based applications using Borland Delphi programming and databases using MySQL. The presence of this application makes it easier for users to search for sales transactions and drug supplies. It is hoped that this new system can make it easier and more efficient for pharmacies to process transaction data and drug stock computerized as well as to facilitate the processing of transaction data and drug stock